Legal Certainty of Abuse of Circumstances as a Basis for Contract Cancellation in Indonesia - Putu Yuliana Kemalasari, Ni (Journal of Comprehensive Science, 2024)
This research discusses the necessity for legal reform in regulating abuse of circumstances within contract law in Indonesia, considering the existing legal vacuum that has the potential to cause uncertainty and injustice in transactions. By analyzing the provisions in the Civil Code (KUHPerdata) and comparing them with the laws of other countries, such as the Netherlands, this study identifies ambiguities and shortcomings in the regulations concerning defects of will, particularly related to abuse of circumstances. The findings indicate that legal uncertainty negatively impacts the bargaining position of the weaker party, creating risks of unfair practices in agreements. Therefore, this research recommends the recognition and clearer regulation of abuse of circumstances to enhance legal protection for vulnerable parties and promote the creation of a fairer and more transparent business environment in Indonesia.